Validation of T2- and diffusion-weighted magnetic resonance imaging for mapping intra-prostatic tumour prior to focal boost dose-escalation using intensity-modulated radiotherapy (IMRT). (December 2019) - Alexander, E.J.; Murray, J.R.; Morgan, V.A.; Giles, S.L.; Riches, S.F.; Hazell, S.; Thomas, K.; Sohaib, S.A.; Thompson, A.; Gao, A.; Dearnaley, D.P.; DeSouza, N.M.
Highlights: 5 mm mapping prostate biopsies correlated with imaged intra-prostatic tumour. Diffusion-restricted tumour of ≥0.5 cm 3 can be dose-escalated with confidence. Tumours of <0.5 cm 3 should not be dose-escalated. Diffusion-weighted MR has good diagnostic accuracy for dominant tumour lesions. Abstract: Background and purpose: To assess the diagnostic accuracy and inter-observer agreement of T2-weighted (T2W) and diffusion-weighted (DW) magnetic resonance imaging (MRI) for mapping intra-prostatic tumour lesions (IPLs) for the purpose of focal dose-escalation in prostate cancer radiotherapy. Materials and methods: Twenty-six men selected for radical treatment with radiotherapy were recruited prospectively and underwent pre-treatment T2W+DW-MRI and 5 mm spaced transperineal template-guided mapping prostate biopsies (TTMPB). A 'traffic-light' system was used to score both data sets. Radiologically suspicious lesions measuring ≥0.5 cm 3 were classified as red; suspicious lesions 0.2–0.5 cm 3 or larger lesions equivocal for tumour were classified as amber. The histopathology assessment combined pathological grade and tumour length on biopsy (red = ≥4 mm primary Gleason grade 4/5 or ≥6 mm primary Gleason grade 3). Two radiologists assessed the MRI data and inter-observer agreement was measured with Cohens' Kappa co-efficient. Results: Twenty-five of 26 men had red image-defined IPLs by both readers, 24 had red pathology-defined lesions. There was a good correlation between lesions ≥0.5 cm 3 classified "red" on imaging and "red" histopathology in biopsies (Reader 1: r  = 0.61, p  < 0.0001, Reader 2: r  = 0.44, p  = 0.03). Diagnostic accuracy for both readers for red image-defined lesions was sensitivity 85–86%, specificity 93–98%, positive predictive value (PPV) 79–92% and negative predictive value (NPV) 96%. Inter-observer agreement was good (Cohen's Kappa 0.61). Conclusions: MRI is accurate for mapping clinically significant prostate cancer; diffusion-restricted lesions ≥0.5 cm 3 can be confidently identified for radiation dose boosting.